Odpowiedzi

Najlepsza Odpowiedź!
2009-10-12T17:03:49+02:00
A) 4(x-5y) + 3(x+8y)= 4x+20y+3x+24y=7x+44y

b) 5(a-2b-1)-3(a-4b)= 5a-10b-5-3a+12b=2a+2b-5

c) 3(x-5)-7(3x-2)+5(7+5x)=3x-15-21x+14+35+25x=7x+34

d) 5a-4(a-3b+1)8+(a-9b)= 5a-4a+12b-4+8a-72b=9a-60b-4

e) 5x+(18+4x+5y)-4(2x+3y)= 5x+18+4x+5y-8x-12y=x+18-7y

f) -(2a-6b+6)-7(2b -3a+2)-5(4a-3b)= -2a+6b-6-14b+21a-14-20a+15b= -a+7b-20


Mam nadzieję ze nigdzie się nie pomyliłam :)
Pozdrawiam :)
2009-10-12T17:20:49+02:00
A) 4x - 20y + 3x + 24y= 4y + 7x
b) 5a - 10b - 5 - 3a + 12b= 2a + 2b - 5
c) 3x - 15 - 21x + 14 + 35 + 25x= 7x + 34
d) 5a - 4a + 12b - 4*8 + a - 9b= 5a - 4a + 12b - 32 + a - 9b= 2a + 3b - 32
e) 5x + 18 + 4x + 5y - 8x -12y= x+18-7y
f) -2a+6b-6-14b+21a-14-20a+15b= -a+7b-20